2022
DOI: 10.1111/jfpp.17031
|View full text |Cite
|
Sign up to set email alerts
|

Development and storage stability of value‐added watermelon fruit butter by incorporating watermelon rind byproduct

Abstract: The main objective of this study was to investigate the incorporation of watermelon rind (WMR) in the form of pulp (15%), powder (10%), and extract (6%) as a value‐added ingredient in the development of WMR‐enriched value‐added watermelon fruit butter. Physicochemical properties (acidity, TSS, and pH), bioactive compounds (total phenolic and flavonoid compounds, lycopene, and citrulline), antioxidant potential (DPPH and FRAP) and microbiological analysis of watermelon fruit butter were evaluated for 60 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The explanation for this result is not clear, but the high temperature involved in the spray drying process could be reason for decrease in the content of bioactive compounds. The reduction in citrulline content could be due to the oxidative reactions that modified the structure of amino acids and the degradation of these amino acid into low molecular weight carboxylic acids (Zia et al, 2022). Higher citrulline loss could happen with increasing levels of watermelon rind present in the spray-drying blends.…”
Section: Lycopene and Citrullinementioning
confidence: 99%
“…The explanation for this result is not clear, but the high temperature involved in the spray drying process could be reason for decrease in the content of bioactive compounds. The reduction in citrulline content could be due to the oxidative reactions that modified the structure of amino acids and the degradation of these amino acid into low molecular weight carboxylic acids (Zia et al, 2022). Higher citrulline loss could happen with increasing levels of watermelon rind present in the spray-drying blends.…”
Section: Lycopene and Citrullinementioning
confidence: 99%
“…Zia et al reported that watermelon by-products have excellent therapeutic properties including anti-diabetic activity, too [214]. It was observed that watermelon rind exhibited anti-diabetic activity by increasing the level of serum insulin and decreasing in level of blood glucose as recommended hypoglycaemic drug in Wistar rats [215,216].…”
Section: Anti-diabetic Health Promoting Effectsmentioning
confidence: 99%
“…Due to their phytochemical enriched profile and potential health benefits, these have recently gained attention [5]. It is necessary to value these by-products to develop some functional products, which can reduce the waste overabundance of increasing populations [6][7][8]. From this perspective, this organic material might be an inexpensive source for developing novel foods, ingredients, or products that reduce waste and adverse environmental effects.…”
Section: Introductionmentioning
confidence: 99%